Charles Bonnet Syndrome Related to a Pituitary Adenoma: A Case Study in a Tunisian Woman - Ghabi, Haifa; Maamri, Amira; Hajri, Ahlem; Zalila, Haifa (Case Reports in Psychiatry, 2023)
According to the International Statistical Classification of Diseases and Related Health Problems 11th Revision (ICD-11) definition, “Charles Bonnet Syndrome” (CBS) refers to the experience of complex visual hallucinations in a person who has experienced a partial or complete loss of vision. Pituitary adenoma is a rare situation that may be associated with CBS. We report a case of CBS in a Tunisian 44-year-old female with pituitary macroadenoma. The patient reported visual hallucinations which persisted after transsphenoidal adenomectomy. She had no prior psychiatric history. She did not take any medication that could produce hallucinations. After Olanzapine initiation, hallucinations were completely resolved. It is the first Tunisian case of CBS reported in English language. This peculiar condition seems to be under-recognized in our country. Clinicians should be aware that visual hallucinations may concern patients without psychiatric disorders.